2018
DOI: 10.1016/j.rppnen.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Learning curve for transbronchial lung cryobiopsy in diffuse lung disease

Abstract: Our findings suggest that proficiency in TBLC is achieved at approximately the 70th procedure; however they need to be validated in more series and cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…In relation to the determination of committee composition, Castillo et al [24] recently reviewed criteria regarding standardization of the necessary professional experience. As for experience, it has been demonstrated that diagnostic yield reflect the TBCB learning curve [25]. Our results reflect TBCB diagnostic yield variability, documented as between 50.6% and 100% in the recently published expert consensus [7].…”
Section: Plos Onesupporting
confidence: 80%
“…In relation to the determination of committee composition, Castillo et al [24] recently reviewed criteria regarding standardization of the necessary professional experience. As for experience, it has been demonstrated that diagnostic yield reflect the TBCB learning curve [25]. Our results reflect TBCB diagnostic yield variability, documented as between 50.6% and 100% in the recently published expert consensus [7].…”
Section: Plos Onesupporting
confidence: 80%
“…However, the presence of pleura does not necessarily mean that the patient will develop a pneumothorax, although the risk is higher. [152857] Thirdly, inadvertent proximal sampling in the absence of fluoroscopy may lead to disruption of major bronchial vessels, resulting in significant bleeding. Finally, fluoroscopic guidance may help in screening for pneumothorax immediately after each biopsy.…”
Section: Methodsmentioning
confidence: 99%
“…Chest radiograph is required to detect a pneumothorax in the postoperative period (generally 2–3 h after the procedure). [175779] Chest ultrasound performed by trained pulmonologists for the detection of pneumothorax following BLC has a sensitivity and specificity of 90% and 94%, respectively,[79] and is superior to a chest radiograph. [80] In a meta-analysis, chest ultrasonography had a pooled sensitivity and specificity of 78.6% (95% CI, 68.1–98.1) and 98.4% (95% CI, 97.3–99.5), respectively, for the detection of pneumothorax; while the sensitivity and specificity of chest radiography was 39.8% (95% CI, 29.4–50.3) and 99.3% (95% CI, 98.4–100), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ravaglia et al [21] proposed a positive correlation of the incidence of pneumothorax with the bronchoscopist’s learning curve. To our knowledge, the only study that investigated how many procedures are necessary to gain a proficiency in TBLC is by Almeida et al [22]. They suggest that a mastery in TBLC is gained after 70 procedures, in terms of sample size, better diagnostic yield, and fewer complications.…”
Section: Learning Curve: How To Learn Tblcmentioning
confidence: 99%